Fetal Movement Counting and Maternal Anxiety: A Systematic Literature Review - Erni Samutri; Lia Endriyani (Alma Ata University Press, 2020)
Perinatal death will decrease maternal quality of life and brought the mother to experience acute grief. Fetal movement count known as a self-screening strategy which may useful to prevent perinatal death and improve pregnancy outcome by increase maternal awareness of decrease fetal activity. On the other hand, this self-screening activity may increase maternal concern, especially maternal anxiety, which the association between these variable are inconsistent. To determine the effect of routine fetal movement counting on maternal anxiety among pregnant women. A comprehensive search was conducted using following database: PubMed, Science Direct and Cochrane Library without any limitation. Evidences about maternal anxiety related to fetal movement were provided by a literature review on the presence of anxiety among women who performing fetal movement count during pregnancy. Five studies were included in this review which consist of four randomized study and one systematic review. All studies were conducted in high income country, which the result may not be generalized in lower-middle income country setting. One RCT (n= 1,013) reported lower worry on fetal movement counting group, one RCT (n= 208) reported significant decrease in state and trait anxiety among counting group, one RCT with small sample (n= 33) found no significant change on state and trait anxiety between control and counting group, one RCT (n= 613) also found no significant change in psychological status among counting group. One systematic review (n=71,458) also reported significant decrease of maternal anxiety among counting group. This review provides sufficient evidence that routine fetal movement counting did not increase maternal anxiety, instead decrease maternal anxiety. Hence, fetal movement counting needs to be introduced to women widely. Further research need to be done in other population, which included lower-middle income country, in order to assess whether fetal movement counting shows positive effect on maternal anxiety in general population.